Optimizing Citizenship Education: Boosting Student Motivation through Make A Match Cooperative Learning Model - Rahayu, Iin (Journal of Social Knowledge Education (JSKE), 2022)
Purpose of the study: This research aims to evaluate the implementation of the Make A Match Type Cooperative Learning Model and its impact on student learning motivation in citizenship education subjects. Methodology: This research is classroom action research, with research time from March 2022 to April 2022. The subjects in this research were class VIII students at One Roof State Junior High School, Baru Village. The instruments in this research consisted of questionnaires and observation sheets. This research procedure consists of several stages which include planning, action, observation and reflection. Data analysis in this research uses descriptive statistics. Main Findings: Based on the recapitulation table of research results, it can be seen that students' learning motivation for citizenship education increases with each cycle. With a value for Cycle I 69.93, Cycle II 80.7 and Cycle III 95.03. At the end of cycle III, it reached a significant increase from the previous two cycles. Therefore, the researcher concluded that one effort to increase the learning motivation of class VIII students at One Roof State Middle School, Baru Village, was to implement the Type Make A Match cooperative learning model. Novelty/Originality of this study: The research highlights the efficacy of the Make A Match Type Cooperative Learning Model in enhancing learning motivation among junior high school students. Utilizing descriptive statistics as an analytical tool, the findings reveal a consistent and significant improvement in student motivation, emphasizing the model's relevance at the junior high school level.